A Comparative Study of the Happiness in Concept of Theravada Buddhism and Roman Catholic Christianity - Kittiwanno, Phraplad Wutthipong (Journal of Thammawat, 2020)
Happiness in perspective of Buddhism means two kinds of happiness, 1) Kâyikasukkha: bodily happiness, which is resulting from economic security, enjoyment of wealth, account of freedom from debt, and account of leading a faultless life or bliss from the five pleasures which is worldly happiness, and 2) Cetasika-sukkha: mental happiness, which is classifying happiness which is resulting from Jhana: absorption and Samâpatti: attainments which are Lokiya-sukkha: mundane happiness. It is greatest. The happiness resulted from attains the enlightenment (Nibbâna) which is the exhaustion of mental intoxicants, because Nibbâna is the greatest bliss which is Lokuttara-sukkha: Supramundane happiness. Happiness in perspective of Christianity means two kinds of happiness as Buddhism. But it is different from Buddhism that it is the part of happiness in this life and next life including the greatest happiness. Christianity thinks that human beings getting happiness have to have love and faith in God with deeply mind, wisdom and thought. When they have love and faith in God, they will be ready to follow the God’s order such Baptism. Then human beings will get salvation which is the salvation from sin and live together with God in the heavenly realms that is no birth, old, sick, and death, it only is mundane happiness, not the same as the ultimate goal (Nibbâna) which is the supramundane happiness.